AI Ethics: A Call for Global Standards in Technology Development - Hoseini, Fatemehsadat (AI and Tech in Behavioral and Social Sciences, 2023)
The development of global standards for ethical AI is not merely a technical issue but a moral imperative that demands immediate and concerted action from all stakeholders involved in AI development and deployment. To navigate the ethical complexities of AI and ensure its benefits are maximized while minimizing its risks, a comprehensive and inclusive approach to AI ethics is essential. This approach must prioritize transparency, accountability, safety, and fairness, and include diverse perspectives to create a truly global ethical framework for AI. As we stand at the crossroads of technological innovation and ethical responsibility, the call for global standards in AI development cannot be overstated. It is time for researchers, policymakers, industry leaders, and the global community to come together to forge a path that ensures AI technologies are developed and used in a manner that upholds the highest ethical standards, respects human rights, and promotes the well-being of society and the environment. In conclusion, the journey towards ethical AI is a collective endeavor that requires the wisdom, insight, and cooperation of the global community. By embracing the challenge of developing and implementing global ethical standards for AI, we can ensure that this transformative technology serves as a force for good, driving progress and innovation in ways that are responsible, ethical, and sustainable.